My Android tablet - Johnston, Craig James, 1967- (Que, 2015)
Full-color, step-by-step tasks walk you through getting and keeping your Android tablet working just the way you want. Learn how to: Take advantage of the new Android 5.0 "Lollipop" features ; Quickly set up your Android tablet and Google account ; Manage all your email accounts, from Gmail to corporate email ; Browse the Web safely and efficiently with new versions of Google Chrome ; Connect and transfer content over Wi-Fi, USB, or Bluetooth ; Search, watch, and upload YouTube videos ; Store your music in the cloud so you can access it anywhere ; Create incredible images with Panorama and Photo Spheres ; Use your built-in camera to record videos ; Organize and track all your meetings, tasks, events, and contacts ; Stay completely up-to-date with Google Now ; Get turn-by-turn navigation help wherever you go ; Find and install great new apps on Google Play ; Buy products and send money with Google Wallet ; Transform your tablet into a world-class e-book reader ; Fix lockups and memory shortages, and keep your tablet up-to-date ; Master Android tips and time-savers for improving your daily life.